MANAGEMENT AND UTILIZATION OF ELECTRONIC INFORMATION RESOURCES IN ALEX EKWUEME LIBRARY, FEDERAL POLYTECHNIC OKO, ANAMBRA STATE, NIGERIA. (NAU Journal of Library and Information Science, 2022)
The study sought to investigate library management and utilization of electronic information resources in Alex Ekwueme Library, Federal Polytechnic Oko in Anambra State. Information and Communication Technology has transformed the way information is created, stored and exchanged and has become a driving force in the 21st Century. This study was guided by six research questions. Descriptive survey research design was used. Population of the study comprised fifty-four (54) library staff of the institution studied. The entire population was studied because the number was considered small and manageable. Hence no sampling was conducted.  Instrument for data collection was a questionnaire. A total of 54 copies of the questionnaire were distributed and same number was returned. The questionnaire contained sixty-one (61) items. Data collected were analyzed using simple percentages and mean(x) scores. A criterion means of 2.50 was used to determine items that received positive rating or otherwise. Findings of the study revealed that management does not make constant provision of electronic information resources (EIRs), as they were identified in the Alex Ekwueme Library, Federal Polytechnic Oko. Based on the findings, the study recommends that the library management should organize training on EIRs on regular, increase the library budget to enhance the acquisition and maintenance of EIRs in Alex Ekwueme Library, Federal Polytechnic Oko, Anambra state, Nigeria. This will enhance the teaching and learning in the institution.
Keywords: Electronic Information Resources; ICT; Polytechnic Libraries; Information Resources Management; Information Resources Utilization; Alex Ekwueme Library